Comparison of the Effects between Tannins Extracted from Different Natural Plants on Growth Performance, Antioxidant Capacity, Immunity, and Intestinal Flora of Broiler Chickens - Song Liu; Kaijun Wang; Senzhu Lin; Zhidan Zhang; Ming Cheng; Shanshan Hu; Hongjie Hu; Jun Xiang; Fengming Chen; Gonghe Li; Hongbin Si (MDPI AG, 2023)
In this study, four plant tannins, including AT (Acacia mearnsii tannin, 68%), CT (Castanea sativa tannin, 60%), QT (Schinopsis lorenzii tannin, 73%) and TT (Caesalpinia spinosa tannin, 50%) were added to broiler diets for 42 days to evaluate and compare their effects on growth performance, antioxidant capacity, immune performance and gut microbiota in broilers. The results showed that the supplementation of five tannins could increase the production of T-AOC, GSH-Px, SOD and CAT and reduce the production of MDA in the serum of broilers (p < 0.01), but the antioxidant effect of the AT group was lower than that of the other three groups (p < 0.01). All four tannins decreased the level of the pro-inflammatory factor IL-1β and increased the level of the anti-inflammatory factor IL-10 (p < 0.01). CT, QT and TT decreased the levels of pro-inflammatory factors IL-6 and TNF-α (p < 0.01), while AT and CT increased the level of IL-2 in serum (p < 0.01). Supplementation with four tannins also increased the levels of IgG, IgM, IgA and sIgA in serum (p < 0.01) and the levels of ZO-1, claudin-1 and occludin in the jejunum (p < 0.01). The detection results of ALT and AST showed that CT, QT and TT decreased the concentrations of ALT and AST in serum (p < 0.01). The results of the gut microbiota showed that the abundance of Clostridia and Subdoligranulum increased, and the abundance of Oscillospiraceae decreased, compared to the control group after adding the four tannins to the diets (p > 0.05). In addition, CT, QT and TT decreased the abundance of Lactobacillus and increased the abundance of Bacteroides compared to the control group, while AT showed the opposite result (p > 0.05). Overall, our study shows that tannins derived from different plants have their own unique effects on broilers. AT and CT can promote broilers' growth better than other tannins, CT has the best ability to improve immune and antioxidant properties, and QT and TT have the best effect on broilers' liver protection.